Evaluation of Machizukuri Process in The Development of Embung Setumpeng Toursim Area, Gentungan Village, Mojogedang District of Karanganyar Regency - Hadi, Syamsul; Kusumaningdyah N.H; Wianto, Ardian Ozzy; Septiyanto, Muhamad Dwi; Prasetyo, Ari; Widiyanti, Emi (JURNAL PENGABDIAN TEKNOLOGI TEPAT GUNA, 2025)
Successful sustainable regional development requires not only the efforts of formal institutions, such as the government but also active community efforts. Therefore, the involvement of the local community is a crucial aspect. This was in line with the Japanese method referred to as Machizukuri. Based on the definition by Evan (2002), Machizukuri is defined as community/neighborhood planning, which implies substantive citizen involvement in autonomous regional planning. Since 2018, the development of the Embung Setumpeng tourism area in Ampel, Gentungan Village, Mojogedang District, Karanganyar Regency has been conducted with many parties. This area development was closely related to the Machizukuri process practiced in Japan, consisting of a bottom-up voluntary process for a common welfare society. To determine the Michizukuri active participant of the villagers, an evaluation was made through joint planning activities in developing the Embung Setumpeng master plan involving the Sebelas Maret University institution in the Matching Fund 2023 activity. The development of the master plan was the beginning of efforts to accomplish the integration of the tourism sector (Pokdarwis Embung Setumpeng), agriculture (Tani Mulyo I), and farm (Tani Mulyo V). The synergistic performance between departments has produced various results, including a grand design master plan, solar power generation, micro-hydro electricity generation, automatic water filtration, recycling of livestock manure into biogas, and the introduction of modern machinery to support organic rice production. The initial step was to conduct field observations and a transect walk, and the second step included interviews with related stakeholders. The third step was conducted a Forum Group Discussion (FGD). This research is expected to find several factors that influence the successful Machizukuri process in developing the Embung Setumpeng tourism area. Keywords: Machizukuri, Co-design, Village Tourism Masterplan, Rural Area